Restructuring process in Vietnam: The road map and initial results - Nguyen, Tu Anh; Nguyen, Thu Thuy (Journal of International Economics and Management, 2014)
Restructuring in Vietnam has become a critical necessity to ensure efficiency and stability, especially in the context of long-lasting recession in the economy as a whole. This paper reviews Vietnam’s economic growth model to point out the demand for restructuring the key blocks of the economy. The paper also discusses the road map for Vietnam’s restructuring process and synthesizes the initial achievements of the process so far.